2016
DOI: 10.3389/fneur.2016.00182
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Subgroups in Bilateral Meniere Disease

Abstract: Meniere disease (MD) is a heterogeneous clinical condition characterized by sensorineural hearing loss, episodic vestibular symptoms, and tinnitus associated with several comorbidities, such as migraine or autoimmune disorders (AD). The frequency of bilateral involvement may range from 5 to 50%, and it depends on the duration of the disease. We have performed a two-step cluster analysis in 398 patients with bilateral MD (BMD) to identify the best predictors to define clinical subgroups with a potential differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 68 publications
(70 reference statements)
4
96
1
5
Order By: Relevance
“…Meanwhile, a discrepancy between autoimmunity and bilaterality was found in this study; systemic autoimmune diseases were not found in BMD patients. Furthermore, the frequency of systemic autoimmune disorders in patients with MD (0.94%) appeared to be much lower than that of Caucasian populations (∼11%), which is significantly higher than the general population . However, autoimmune pathology can be confined to the inner ear, which is unlikely to manifest as systemic symptoms.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Meanwhile, a discrepancy between autoimmunity and bilaterality was found in this study; systemic autoimmune diseases were not found in BMD patients. Furthermore, the frequency of systemic autoimmune disorders in patients with MD (0.94%) appeared to be much lower than that of Caucasian populations (∼11%), which is significantly higher than the general population . However, autoimmune pathology can be confined to the inner ear, which is unlikely to manifest as systemic symptoms.…”
Section: Discussionmentioning
confidence: 82%
“…In bilateral cases, intratympanic steroid injections and endolymphatic sac surgeries were chosen for the second‐line treatment for the second‐involved ear. Patients with simultaneous bilateral involvement with an interval shorter than 1 month between the first‐ and second‐ear involvement were considered to have synchronous BMD, and other bilateral involvements were categorized as metachronous BMD …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an interesting cluster analysis on bilateral Meniere disease was published to define clinical subgroups with potential similar etiologies. In this study, five clinical variants of bilateral Meniere disease were found based on six clinical variables and with a high silhouette measure of 0.8 (9). This study is not only beneficial to improve the selection of patients but also can explain the negative treatment effects of several treatment trials, as results can be biased by a heterogeneous patient group based on etiology (9).…”
Section: Discussionmentioning
confidence: 87%
“…In this study, five clinical variants of bilateral Meniere disease were found based on six clinical variables and with a high silhouette measure of 0.8 (9). This study is not only beneficial to improve the selection of patients but also can explain the negative treatment effects of several treatment trials, as results can be biased by a heterogeneous patient group based on etiology (9). The difficulty in cluster analysis is that it is a type of analysis that is very sensitive to change of variables.…”
Section: Discussionmentioning
confidence: 87%